2013
DOI: 10.1074/jbc.m112.417071
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroendocrine Protein 7B2 Suppresses the Aggregation of Neurodegenerative Disease-related Proteins

Abstract: Background: The neuroendocrine protein 7B2 blocks the aggregation of certain secreted proteins.Results: 7B2 co-localizes with protein aggregates in Parkinson and Alzheimer disease brains; blocks the fibrillation of Aβ1–40, Aβ1–42, and α-synuclein; and blocks Aβ1–42-induced Neuro-2A cell death.Conclusion: 7B2 inhibits the cytotoxicity of Aβ1–42 by modulation of oligomer formation.Significance: 7B2 is a novel anti-aggregation secretory chaperone associated with neurodegenerative disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 54 publications
2
50
0
Order By: Relevance
“…This phenomenon has previously been demonstrated for the secretory proteins chromogranins A [3941] and B [42, 43], proteins which have been proposed to assist in granule formation and efficient hormone storage. While these two secretory granule proteins do not structurally resemble 7B2, all have been termed “granins” due to the presence of a specific acidic amino acid motif [44], and 7B2 has known secretory chaperone effects [45, 46]. However, in our radiolabeling experiments of 7B2- and FGF23-transfected SW3 cells, we did not detect increased cellular FGF23 storage.…”
Section: Discussionmentioning
confidence: 54%
“…This phenomenon has previously been demonstrated for the secretory proteins chromogranins A [3941] and B [42, 43], proteins which have been proposed to assist in granule formation and efficient hormone storage. While these two secretory granule proteins do not structurally resemble 7B2, all have been termed “granins” due to the presence of a specific acidic amino acid motif [44], and 7B2 has known secretory chaperone effects [45, 46]. However, in our radiolabeling experiments of 7B2- and FGF23-transfected SW3 cells, we did not detect increased cellular FGF23 storage.…”
Section: Discussionmentioning
confidence: 54%
“…Previous work in our laboratory has shown that the secretory chaperone 7B2 not only colocalizes with amyloid plaques but also inhibits beta amyloid fibrillation [18]. Since 7B2 is abundant in the pancreas [26] we investigated the possibility that 7B2 may also inhibit hIAPP fibrillation.…”
Section: Resultsmentioning
confidence: 99%
“…As the tissue distributions of 7B2 and proSAAS are much broader than those of the convertases [17], additional functions are currently being investigated. The recent discovery of 7B2 as a potent inhibitor of beta amyloid and synuclein aggregation supports the idea that this family of chaperones may serve as general secretory chaperones, acting to prevent aggregation of proteins in AD and PD [18] and possibly in other diseases which involve amyloid formation.…”
Section: Introductionmentioning
confidence: 93%
“…Overexpression or exogenous addition of a variety of chaperone proteins is efficacious in delaying or preventing amyloid fibril generation both in in vitro and, more recently, in vivo models of various amyloidogenic diseases (39)(40)(41). However, the chaperones tested to date are ubiquitously expressed, and thus far no neuron-specific chaperone protein has been shown to have antiaggregant activity against amyloidogenic diseases such as PD.…”
Section: Discussionmentioning
confidence: 99%